Polishing layer, polishing pad and polishing method
By using a polishing layer made of a polyurethane substrate to control its microscopic contact area and surface roughness, the shortcomings of existing polishing pads in various processes are solved, and a more efficient polishing process and a lower defect rate are achieved.
Patent Information
- Application Number
- CN202510005327.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-13
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The existing polishing pads have shortcomings in the control of micro-contact area and surface roughness, which is difficult to meet the needs of various processes, affecting the efficiency and quality of the CMP polishing process.
A polishing layer made of a uniform closed-pore elastic body formed of a polyurethane substrate with pore separation continuous, is adopted, and the surface contains a microconvex body. By controlling the microcontact area ratio and contact coefficient, the controllability of the microcontact area and surface roughness of the polishing pad is achieved.
Under the pressure conditions of 1 psi to 20 psi, the micro-contact area ratio between the polished layer and the polished object is between 0.01% and 5%, which improves the polishing rate and reduces the defect rate, and is suitable for a variety of semiconductor processes.
Smart Images

Figure CN119734199A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polishing of chemical mechanical planarization treatment, and in particular to a polishing pad and a method for manufacturing a semiconductor device. Background Art
[0002] CMP technology is a technology that places the surface of the device to be processed facing downward, applies a certain pressure to the polishing pad, and under the action of the polishing liquid, uses the relative movement of the polishing pad and the device to be processed to remove the material on the surface of the device to be processed through mechanical grinding of the abrasive particles and chemical corrosion of the oxidant, thereby obtaining a flat surface.
[0003] With the development of the semiconductor industry, the trend of processing technology is shifting towards higher current density, higher clock frequency and more interconnection layers. Due to the reduction of the size of the chip and the reduction of the focal depth of the lithography equipment, the flatness of the acceptable resolution of the chip surface is required to reach the nanometer level. Traditional flattening technologies such as selective deposition based on deposition technology, sputtered glass SOG, low-pressure CVD, plasma-enhanced CVD and other technologies can also provide a smooth surface, but they are all local flattening technologies and cannot achieve global flattening. It is generally believed internationally that when the device feature size is below 0.35μm, global flattening must be performed to ensure the accuracy and resolution of the lithography transmission. CMP technology is currently recognized internationally as the only technology that can achieve global flattening. The CMP yield seriously affects the yield of the chip.
[0004] Polishing pads are one of the final consumables in CMP and are widely used in integrated circuit manufacturing. The polishing pads currently used are mainly made of polymer materials, and their main component is foamed and cured polyurethane. The surface of these polishing pads not only has a certain density of micro-convex bodies, but also has many hollow micropores. Their surface structural characteristics (roughness, groove shape, etc.) and material (hardness, elastic modulus, etc.) are important factors affecting CMP. In practical applications, the surface roughness of the polishing pad often shows obvious changes with the consumption of materials, and the microscopic contact area between the polishing pad and the object to be polished also affects the CMP polishing process.
[0005] There is an urgent need to develop a polishing pad that is suitable for a variety of processes and has controllable micro-contact area and surface roughness. Summary of the invention
[0006] In order to solve the problems in the prior art, the present invention provides a polishing layer in a first aspect, wherein the polishing layer is a uniform closed-cell elastomer formed of a polyurethane substrate having continuous pore separation, the surface of the polishing layer comprises micro-convex bodies, the micro-convex bodies are in substantial contact with the object to be polished to form a microscopic contact surface, and the polishing layer has a microscopic contact area ratio between the polishing layer and the object to be polished at a pressure of 1 psi to 20 psi, which is between 0.01% and 5%;
[0007] Furthermore, under the pressure condition of 1 psi to 10 psi, the contact coefficient ζ=(microscopic contact area ratio between the polishing layer and the object to be polished / density of the polishing layer)*100, and the contact coefficient ζ is between 0.1 and 1.2;
[0008] As a preferred embodiment, under the pressure condition of 1psi to 5psi, the contact coefficient ζ of the polishing layer is (microscopic contact area ratio between the polishing layer and the object to be polished / density of the polishing layer)*100, and the contact coefficient ζ is between 0.1 and 0.7;
[0009] Furthermore, the roughness of the polishing layer is between 1 μm and 30 μm;
[0010] Preferably, the roughness of the polishing layer is between 2 μm and 15 μm;
[0011] Furthermore, the density of the polishing layer is between 0.4 g / cm 3 ~1.1g / cm 3 The hardness of the polishing layer is between 10D and 75D;
[0012] Further, the polishing layer comprises a reaction product of an isocyanate-terminated prepolymer and a curing agent, and the isocyanate-terminated prepolymer comprises a reaction product of a multifunctional isocyanate and a polyol;
[0013] Further, the multifunctional isocyanate comprises one or more combinations of 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, ethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, 1,4-cyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, and norbornane diisocyanate;
[0014] Preferably, the multifunctional isocyanate comprises one or more combinations of 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate;
[0015] Further, the polyol comprises one or more combinations of polytetramethylene ether glycol, polyethylene glycol, polypropylene glycol, ethylene glycol, butanediol, diethylene glycol, neopentyl glycol, 2-methyl-1,3-propanediol, hexanediol, 3-methyl-1,5-pentanediol, 1,4-cyclohexanedimethanol, homopolymers and / or copolymers of ethylene oxide and propylene oxide;
[0016] Preferably, the polyol comprises one or more combinations of polytetramethylene ether glycol, polypropylene glycol, diethylene glycol, homopolymers and / or copolymers of ethylene oxide and propylene oxide;
[0017] Further, the curing agent comprises a polyamine curing agent;
[0018] The polyamine curing agent includes diethyltoluenediamine (DETDA), N,N'-dialkyldiaminodiphenylmethane, 3,5-diethyl-2,4-toluenediamine and its isomers (e.g., 3,5-diethyl-2,6-toluenediamine), 3,5-dimethylthio-2,4-toluenediamine and its isomers, 4,4'-methylene-bis-(2-chloroaniline) (MOCA), 4,4'-bis-(sec-butylamino)-diphenylmethane, 1,4-bis-(sec-butylamino)-benzene, 4,4'-methylene-bis-(2-chloroaniline), 4,4'-methylene-bis-(sec-butylamino)-benzene. (3-chloro-2,6-diethylaniline) (MCDEA), polyoxytetramethylene-di-p-aminobenzoate; p,p'-methylenedianiline (MDA); metaphenylenediamine (MPDA); 4,4'-methylene-di-(2,6-diethylaniline) (MDEA), 4,4'-methylene-di-(2,3-dichloroaniline) (MDCA), 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, 2,2',3,3'-tetrachlorodiaminodiphenylmethane, propylene glycol-di-p-aminobenzoate or one or more combinations thereof;
[0019] Particularly preferably, the polyamine curing agent is 4,4'-methylene-bis-(2-chloroaniline) (MOCA);
[0020] Furthermore, the unreacted NCO of the isocyanate-terminated prepolymer is between 8.0% and 9.5%, and the stoichiometric ratio of NH2 to NCO of the isocyanate-terminated prepolymer is between 80% and 105%.
[0021] A second aspect of the present invention provides a polishing pad, which includes the above-mentioned polishing layer. In addition, the polishing pad also includes an intermediate rubber layer, a buffer layer and a release film layer. When the polishing pad is under a pressure of 1psi to 20psi, the microscopic contact area ratio between the polishing pad and the polished object is between 0.01% and 5%.
[0022] The third aspect of the present invention provides a polishing method, providing a polished object, wherein the polished object is selected from at least one of a magnetic substrate, an optical substrate or a semiconductor substrate, providing the above-mentioned polishing pad, forming dynamic contact between the polishing surface of the polishing layer and the polished object to polish the surface of the polished object, and using a dresser to dress the polishing surface.
[0023] The present invention controls the microscopic contact area between the polishing layer and the object to be polished within a certain range, so that the polishing pad prepared can obtain a good polishing rate and a low defect rate in the process of polishing semiconductor devices. Further, by controlling the contact coefficient ζ within a certain range, the grinding rate non-uniformity can be effectively improved. The polishing pad is suitable for a variety of semiconductor processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 A microscopic schematic diagram of a cross section of the polishing layer and a schematic diagram of a contact surface with an object to be polished according to the present invention;
[0026] Figure 2 A schematic diagram of the application of the polishing pad provided in the embodiment of the present invention;
[0027] Figure 3 A schematic diagram of a polishing pad provided in an embodiment of the present invention;
[0028] Figure 4 A schematic diagram of sampling for measuring the micro-contact area ratio of a polishing pad or a polishing layer according to an embodiment of the present invention;
[0029] 1- material to be polished; 2- polishing pad; 3- polishing machine; 4- bracket; 5- polishing liquid; 20- polishing layer; 21- adhesive layer; 22- back adhesive layer; 23- buffer layer; 201- micro-convex body; 202- contact part; 203- contact surface. DETAILED DESCRIPTION
[0030] The invention provides a polishing layer, which is a uniform closed-cell elastomer formed by a polyurethane substrate with continuous pore separation. The surface of the polishing layer comprises micro-convex bodies, which are in substantial contact with an object to be polished to form a microscopic contact surface. Under a pressure condition of 1psi to 20psi, the microscopic contact area ratio between the polishing layer and the object to be polished is between 0.01% and 5%.
[0031] Since the polishing layer is a polyurethane material, its surface often exhibits a certain degree of roughness and unevenness relative to the surface of the object being polished. This surface characteristic causes the uneven rough peaks of the polishing layer to contact the object being polished. The two are not in a completely fitted state, and local contact points will be formed. The number and size of the local contact points will affect the polishing rate. Therefore, the microscopic contact area ratio involved in the present invention is the ratio of the actual contact area between the polishing layer and the object being polished to the area of the polishing layer surface under certain pressure conditions; the polyurethane material in the present invention is homogeneous, so the microscopic contact area ratio of the polishing layer part can be used to reflect the microscopic contact area ratio of the entire polishing layer.
[0032] As a method for measuring the micro-contact area ratio, a conventional test method in the art may be selected.
[0033] As an example of a test method, the present invention can be carried out using the following method:
[0034] To prepare a sample for testing the microscopic contact area rate, first wipe the surface of the polishing pad or the polishing layer with anhydrous ethanol, then blow dry it with a blow-drying device, and use a mold with a diameter of 10 mm to 20 mm to cut out a circle with a diameter of 10 mm to 20 mm on the polishing pad or the polishing layer to be tested. When sampling, ensure that the sampling is done in the same area. After preparing the sample, observe whether the surface of the sample is flat. The area with grooves or the area without grooves on the surface of the polishing pad or the polishing layer can be used. It should be noted that the area with grooves or the area without grooves, when using the area with grooves, the area of the grooves needs to be deducted in data processing. The grooves are carriers for carrying the abrasive composition and polishing debris, and they do not actually contact the object to be polished during the polishing process. Therefore, when calculating the actual microscopic contact area rate, the projected area of the grooves is also deducted.
[0035] Microscopic contact area rate sampling: Take 14 to 20 groups of photos on the surface of a 10 mm to 20 mm circular test sample. Preferably, 6 groups of photos in the middle of the circular test sample, 4 groups of photos on the left and right, a total of 14 groups of photos, and average the calculated microscopic contact area rates to infer the microscopic area contact rate of the polishing pad or polishing layer as a whole, such as Figure 4 shown.
[0036] Motion device: The Z-axis of the test system uses the GMT standard electric slide table (AXS60-A2NR-DD) from Taiwan, China. The motion stroke is ±10mm, the table size is 60mm*60mm, and the unidirectional positioning accuracy is 15μm. The motion control department uses a combination of SMC30PLC controller and SMC72XL Hall control rod; the sensor uses an S-type force sensor (SMT1-10N, INTERFACEUSA).
[0037] Optical device: Inverted metallographic microscope (LC-230DZ, Shenzhen Lichuang Instrument Co., Ltd.).
[0038] Software algorithm: The polishing pad micro-contact measurement software based on MATLAB 2020a is used to calculate the images taken by the metallographic microscope to obtain the micro-contact area rate.
[0039] The above test method is only one of many test methods in the art, and the present invention does not make any limitation thereto. It should be noted that any test method that can implement the present invention can be applied to the present invention.
[0040] Preferably, in the embodiment of the present invention, considering the application of the polishing process, the microscopic contact area ratio between the polishing layer and the object to be polished is between 0.1% and 1% under the pressure condition of 1 psi to 17 psi.
[0041] Preferably, in the embodiment of the present invention, for consideration of appropriate pressure in the polishing process, the polishing layer has a microscopic contact area ratio with the object to be polished of between 0.1% and 0.6% under a pressure of 1 psi to 10 psi.
[0042] Preferably, in the embodiment of the present invention, due to the appropriate polishing process and its suitable pressure, as well as the higher removal rate and relatively fewer defects, the microscopic contact area ratio of the polishing layer and the polished object is between 0.4% and 0.5% under the pressure condition of 9psi to 10psi.
[0043] Preferably, in the embodiment of the present invention, for the sake of minimal defects, the polishing layer has a microscopic contact area ratio between the polishing layer and the object being polished ranging from 0.5% to 0.8% under a pressure of 9psi to 10psi.
[0044] Preferably, in the embodiment of the present invention, for the sake of extremely high removal rate, the polishing layer has a microscopic contact area ratio with the object to be polished between 0.3% and 0.4% under a pressure of 9psi to 10psi.
[0045] In the present invention, for the consideration of low grinding rate non-uniformity, the polishing layer is under a pressure of 1 psi to 10 psi, and the contact coefficient ζ = (microscopic contact area ratio between the polishing layer and the object to be polished / density of the polishing layer)*100, and the contact coefficient ζ is between 0.1 and 1.2;
[0046] Preferably, in the present invention, for the sake of lower grinding rate non-uniformity, the contact coefficient ζ of the polishing layer under a pressure of 1psi to 5psi is = (microscopic contact area ratio between the polishing layer and the object to be polished / density of the polishing layer)*100, and the contact coefficient ζ is between 0.1 and 0.7.
[0047] In the embodiments of the present invention, the roughness of the polishing layer is between 1 μm and 30 μm; preferably, in the embodiments of the present invention, the roughness of the polishing layer is between 2 μm and 15 μm.
[0048] In consideration of appropriate polishing process pressure, higher removal rate and relatively fewer defects, it is particularly preferred that the roughness of the polishing layer in the embodiment of the present invention is between 8 μm and 10 μm.
[0049] Considering the minimum defects, it is particularly preferred that the roughness of the polishing layer in the embodiment of the present invention is between 10 μm and 15 μm.
[0050] Considering the extremely high removal rate, it is particularly preferred that the roughness of the polishing layer in the embodiment of the present invention is between 2 μm and 8 μm.
[0051] The density of the polishing layer in the embodiment of the present invention is between 0.4 g / cm 3 ~1.1g / cm 3 The hardness of the polishing layer is between 10D and 75D;
[0052] Preferably, the density of the polishing layer in the embodiment of the present invention is between 0.5 g / cm 3 ~0.9g / cm 3 In particular, the density of the polishing layer in the embodiment of the present invention is preferably between 0.7 g / cm 3 ~0.9g / cm 3 between.
[0053] Preferably, the hardness of the polishing layer in the embodiment of the present invention is between 40D and 70D, and particularly preferably, the hardness of the polishing layer in the embodiment of the present invention is between 55D and 70D.
[0054] The polishing layer in the present invention comprises a reaction product of an isocyanate-terminated prepolymer and a curing agent, and the isocyanate-terminated prepolymer comprises a reaction product of a multifunctional isocyanate and a polyol.
[0055] Multifunctional isocyanate
[0056] In the embodiment of the present invention, the polyfunctional isocyanate includes but is not limited to one or more combinations of aromatic isocyanates or aliphatic isocyanates. It is preferred to use more than 80 mol % of aromatic isocyanates, more preferably more than 95 mol % of aromatic isocyanates, and particularly preferably 100 mol % of aromatic isocyanates.
[0057] The aromatic isocyanate includes one or more combinations of 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, p-xylylene diisocyanate, and m-xylylene diisocyanate.
[0058] The aliphatic isocyanate includes one or more combinations of ethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, 1,4-cyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, and norbornane diisocyanate.
[0059] In the embodiment of the present invention, considering the reaction activity and the physical properties of the polishing layer, it is preferred to use one or more combinations of 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.
[0060] In the embodiment of the present invention, considering the reaction activity and the physical properties of the polishing pad, it is particularly preferred to use one of 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4-dicyclohexylmethane diisocyanate or a combination of the two.
[0061] Polyols
[0062] In the embodiment of the present invention, the polyol may include a high molecular weight diol based on polyether, wherein the high molecular weight diol based on polyether includes but is not limited to polytetramethylene ether glycol (PTMEG), polyethylene glycol (PEG), polypropylene glycol (PPG) and one or more combinations of polytetramethylene ether glycol-polyethylene glycol, polytetramethylene ether glycol-polypropylene glycol, polyethylene glycol-polypropylene glycol, homopolymers and / or copolymers of ethylene oxide and propylene oxide, or a high molecular weight polyol formed by homopolymerization or copolymerization of ethylene glycol, propylene glycol, butanediol or an initiator having two hydroxyl groups with the above three small molecule diols, or a variety of combinations.
[0063] In the embodiment of the present invention, the polyol may include a small molecule diol, wherein the small molecule includes but is not limited to one or more combinations of ethylene glycol, butanediol, diethylene glycol, neopentyl glycol, 2-methyl-1,3-propanediol, hexanediol, 3-methyl-1,5-pentanediol, and 1,4-cyclohexanedimethanol.
[0064] In the embodiment of the present invention, the polyol composition may further include a polyester-based polyol, wherein the polyester-based polyol is obtained by a condensation reaction of a diol or a diol / phenol with a dibasic acid, wherein the diol includes ethylene glycol, 1,3-butanediol, 1,4-butanediol, diethylene glycol, neopentyl glycol, 2-methyl-1,3-propanediol, hexanediol, 3-methyl-1,5-pentanediol, 1,4-cyclohexanedimethanol, or one or more combinations thereof. Preferably, the diol includes 1,4-butanediol, one or a combination of hexanediol; the diol / phenol is one or a combination of hydroquinone, resorcinol, naphthalene diol, bisphenol A, bisphenol S, terephthalic acid, isophthalic acid, o-phthalic acid, 2,5-furan dimethanol, terephthalic acid or diphenyl ether diphenol. Preferably, the diol / phenol is one or a combination of hydroquinone and terephthalic acid; the dibasic acid is one or a combination of succinic acid, adipic acid, azelaic acid and sebacic acid.
[0065] In the embodiment of the present invention, considering the reactivity and physical properties of the polishing pad, one or more combinations of polytetramethylene ether glycol (PTMEG), diethylene glycol, butanediol or homopolymers and / or copolymers of ethylene oxide and propylene oxide are preferably used.
[0066] In the embodiments of the present invention, considering the reactivity and physical properties of the polishing pad, it is particularly preferred to use one of polytetramethylene ether glycol (PTMEG) and diethylene glycol or a combination of the two.
[0067] The isocyanate-terminated prepolymer can be obtained by reacting the multifunctional isocyanate with a polyol, or by purchasing a commercially available prepolymer product.
[0068] Commercially available isocyanate-terminated prepolymers include, but are not limited to, any one or more combinations of the series of prepolymers produced by Chemtura: LF800A, LF900A, LF910A, LF930A, LF931A, LF939A, LF950A, LF952A, LF600D, LF601D, LF650D, L42, L325, L100, L150, L167, L200, L275, L300, L310, L367, L480, L500, LF667, LF667D, LF700D, LF750D, LF751D, LF752D, LF753D, LFG963A, LFG964A, and LFG740D.
[0069] Curing agent
[0070] In the embodiment of the present invention, the curing agent is selected from one or more combinations of polyamine curing agents or polyol curing agents. The present invention has no particular limitation on the polyamine curing agent or the polyol curing agent, and can be any suitable aromatic bifunctional curing agent or polyol curing agent in the art.
[0071] Examples of polyamine curing agents that can be used in embodiments of the present invention include diethyltoluenediamine (DETDA), N,N'-dialkyldiaminodiphenylmethane, 3,5-diethyl-2,4-toluenediamine and its isomers (e.g., 3,5-diethyl-2,6-toluenediamine), 3,5-dimethylthio-2,4-toluenediamine and its isomers, 4,4'-methylene-bis-(2-chloroaniline) (MOCA), 4,4'-bis-(sec-butylamino)-diphenylmethane, 1,4-bis-(sec-butylamino)-benzene, 4,4'-methylene-bis-(2-chloroaniline), 4,4'- One or more combinations of methylene-bis-(3-chloro-2,6-diethylaniline) (M-CDEA), polyoxytetramethylene-di-p-aminobenzoate; p,p'-methylenedianiline (MDA); metaphenylenediamine (MPDA); 4,4'-methylene-di-(2,6-diethylaniline) (MDEA), 4,4'-methylene-di-(2,3-dichloroaniline) (MDCA), 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, 2,2',3,3'-tetrachlorodiaminodiphenylmethane, propylene glycol-di-p-aminobenzoate.
[0072] In order to ensure that the polishing pad has a suitable operating time during preparation and the obtained polishing pad has good polishing performance, preferably, the polyamine curing agent contains one or a combination of 4,4'-methylene-bis-(2-chloroaniline) (MOCA) and 4,4'-methylene-bis-(3-chloro-2,6-diethylaniline) (M-CDEA); particularly preferably, the polyamine curing agent contains 4,4'-methylene-bis-(2-chloroaniline) (MOCA).
[0073] Hollow microsphere polymer
[0074] In the process of preparing the polishing layer, the hollow microsphere polymer is usually evenly dispersed in the polishing layer, so as to adjust the polishing effect of the polishing layer.
[0075] The term "hollow microsphere polymer" in the embodiments of the present invention refers to an expandable hollow polymer microsphere that can moderately expand during the curing process by virtue of the temperature increase caused by the reaction exotherm. The polishing performance of the polishing layer can be further adjusted by adjusting the distribution mode (such as density) of the hollow microsphere polymer in the polyurethane polishing layer and adjusting the particle size of the hollow microsphere polymer. Preferably, the hollow microsphere polymer is dispersed in the polishing layer so that the final porosity of the polishing layer is 10% to 65%.
[0076] Preferably, the hollow microsphere polymer includes but is not limited to a vesicular structure having an outer wall of polyacrylonitrile and polyacrylonitrile copolymer, and can be purchased from microspheres or microbeads of any company of Akzo Nobel, Matsumoto Oil & Fat Pharmaceutical Co., Ltd. or Sekisui Chemical Co., Ltd. Particularly preferably, in the embodiment of the present invention, Akzo Nobel hollow microspheres or Matsumoto microbeads F series are selected.
[0077] In the embodiment of the present invention, the unreacted NCO content of the isocyanate-terminated prepolymer is between 8.0% and 9.5%. Preferably, the unreacted NCO content of the isocyanate-terminated prepolymer is between 8.5% and 9.5%.
[0078] In the embodiment of the present invention, the stoichiometric ratio of NCO of the isocyanate-terminated prepolymer of NH2 and / or OH in the curing agent is between 80% and 105%; preferably, the stoichiometric ratio of NCO of the isocyanate-terminated prepolymer of NH2 and / or OH in the curing agent is between 80% and 100%.
[0079] The polishing pad involved in the present invention comprises the above-mentioned polishing layer. In addition, the polishing pad further comprises an intermediate rubber layer, a buffer layer and a release film layer. Under the pressure condition of 1psi to 20psi, the microscopic contact area ratio between the polishing pad and the object to be polished is between 0.01% and 5%. Figure 2 The polishing pad shown includes a polishing layer 20, an intermediate rubber layer 21, a buffer layer 22 and a release film layer 23; after the polishing layer is attached to the buffer layer and the release film layer, the microscopic contact area ratio of the polishing pad relative to the polishing layer will increase slightly.
[0080] In the present invention, appropriate modifiers may be added to the polyurethane substrate to obtain more excellent comprehensive performance improvement. Preferably, these modifiers can change at least one property of the polishing layer, and the above properties include but are not limited to the group consisting of the following items: porosity, rigidity, surface energy, wear resistance, conductivity, and chemical function. Modified materials include but are not limited to: antioxidants, lubricants, pigments, fillers, antistatic agents, etc.
[0081] In the present invention, the polishing layer may be provided with grooves according to the conventional art, and the grooves are used to receive the polishing liquid during the polishing process. The grooves can be obtained by processing after the polishing layer is formed. The arrangement of the grooves can ensure the smooth discharge and flow of the polishing liquid used in the polishing process. Preferably, the grooves are one or more of concentric grooves (for example, annular or spiral grooves), curved grooves, grid line grooves, regular polygonal grooves (for example, hexagonal, triangular), and tire surface patterns. Particularly preferably, the grooves are one or more of annular grooves, spiral grooves, X-Y grid grooves, hexagonal grooves, triangular grooves and fractal grooves. Particularly preferably, the cross-section of the groove is one or more of a straight sidewall rectangle, a "V" shape, a "U" shape and a zigzag shape.
[0082] Optionally, the width of the groove is 0.1-0.6 mm, the depth of the groove is 0.5-0.9 mm, the spacing between adjacent grooves is 2-5 mm, a central blank area may be provided or not provided, wherein the radius of the central blank area is 50 mm-150 mm.
[0083] In CMP, a buffer layer is required to take into account both planarity and uniformity, which are in a compromise relationship. Planarity refers to the flatness of the pattern portion when polishing a polished material having micro-concave and convex portions generated during pattern formation, and uniformity refers to the uniformity of the entire polished material. The planarity is improved by utilizing the characteristics of the polishing layer, and the uniformity is improved by utilizing the characteristics of the buffer layer. In the polishing pad of the present invention, the buffer layer is preferably made of a material softer than the polishing layer.
[0084] Examples of the cushioning layer include fiber nonwoven fabrics such as polyester nonwoven fabrics, nylon nonwoven fabrics, and acrylonitrile nonwoven fabrics, resin impregnated nonwoven fabrics such as polyester nonwoven fabrics impregnated with polyurethane, polymer resin foams such as polyurethane foam and polyethylene foam, rubber resins such as butadiene rubber and isoprene rubber, and photosensitive resins.
[0085] As a method for bonding the polishing layer and the buffer layer, an intermediate glue is used. The intermediate glue can be a double-sided tape. The polishing layer and the buffer layer are placed on both sides of the intermediate glue for pressing.
[0086] The polishing pad of the present invention also includes a back adhesive layer, and a double-sided tape can be used as the back adhesive layer. As the composition of the back adhesive layer, for example, a rubber adhesive, an acrylic adhesive, etc. can be listed. Considering the content of metal ions, acrylic adhesives have less metal ion content, so they are preferred.
[0087] The adhesive layer in the present invention further comprises a release film or a release paper, and the release film or the release paper can be torn off before use to achieve the bonding of the polishing pad and the polishing machine.
[0088] The polishing layer in the embodiment of the present invention may be provided with an endpoint detection window according to actual needs. Optionally, at least one endpoint detection area may be formed in the polishing layer. When the polishing operation is performed, the endpoint detection area of the polishing layer can perform high-precision optical endpoint detection, and the detection method may be optical detection. The endpoint detection area is made of a suitable material so that it has a suitable light transmittance to observe the polished object (such as a silicon wafer). As a preferred embodiment, the material forming the endpoint detection area has a light transmittance of not less than 20% in the entire range of wavelengths of 300 to 800. More preferably, the light transmittance of the high-transmittance material is not less than 60%.
[0089] As a preferred embodiment, the material of the endpoint detection area includes but is not limited to thermosetting resins such as polyurethane resin, polyester resin, phenol resin, urea resin, melamine resin, epoxy resin and acrylic resin; one or more combinations of polyurethane resin, polyester resin, polyamide resin, cellulose resin, acrylic resin, polycarbonate resin, halogen-containing resin (polyvinyl chloride, polytetrafluoroethylene and polyvinylidene fluoride, etc.), polystyrene and olefin resin (polyethylene, polypropylene, etc.) thermoplastic resins.
[0090] <Polishing>
[0091] The polishing pad involved in the present invention can be applied to commonly used semiconductor processes. Examples of common processes include but are not limited to: STI process, oxide process, W process, Al process, copper process, and poly process.
[0092] Polishing: Use Figure 1 The polishing device shown in the figure is carried out, and the polishing device has a polishing machine table 3 supporting a polishing pad 2, a support 4 supporting a material to be polished-a semiconductor wafer 1 and a backing material for uniformly pressurizing the wafer, and a supply mechanism for a polishing liquid 5. The polishing pad 2 is mounted on the polishing machine table 3, for example, by adhering a backing layer. The polishing machine table 3 and the support 4 are configured so that the polishing pad 2 and the semiconductor wafer 1 supported by each are opposite to each other, and each has a rotation axis. In addition, a pressurizing mechanism for pressing the semiconductor wafer 1 onto the polishing pad 2 is provided on one side of the support 4. When polishing, the polishing machine table 3 and the support 4 are rotated, and the semiconductor wafer 1 is pressed onto the polishing pad 2, and polishing is performed while supplying slurry. There are no special restrictions on the flow rate of the slurry, the polishing load, the rotation speed of the polishing machine table, and the rotation speed of the wafer, and they can be adjusted appropriately.
[0093] The polishing method involved in the present invention provides a polished object, which is selected from at least one of a magnetic substrate, an optical substrate or a semiconductor substrate, provides the above-mentioned polishing pad, forms dynamic contact between the polishing surface of the polishing layer and the polished object, thereby polishing the surface of the polished object, and uses a dresser to dress the polishing surface.
[0094] Example
[0095] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0096] Explanation of the reference numerals in the embodiments:
[0097] LF750D, LFG963A: respectively represent Chemtura Corporation LF750D isocyanate terminated prepolymer; LFG963A isocyanate terminated prepolymer; LF667 isocyanate terminated prepolymer;
[0098] MOCA: 4,4'-methylene-bis-(2-chloroaniline);
[0099] DEG: diethylene glycol;
[0100] TDI: toluene diisocyanate;
[0101] HMDI: 4,4'-dicyclohexylmethane diisocyanate;
[0102] PTMEG: polytetramethylene ether glycol;
[0103] 920DE 40d30: Nouryon 920DE 40d30, average particle size 40μm, density 0.03g / cm 3 ;
[0104] 920DET 40d25: Nouryon 920DET 40d25, average particle size 40μm, density 0.025g / cm 3 ;
[0105] 920DE 80d30: Nouryon 920DE 80d30, average particle size 80μm, density 0.03g / cm 3 ;
[0106] 043DET 80d20: Nouryon 043DET 80d20, average particle size 80μm, density 0.02g / cm 3 ;
[0107] The above-mentioned raw materials without trademark origin are all from bulk industrial products on the market, and the manufacturers include BASF, Covestro, Wanhua Chemical, Suzhou Xiangyuan, Chizhou Tianci, Mitsui Chemicals, Mitsubishi Chemical, etc.
[0108] Example 1
[0109] This embodiment provides a polishing pad, and the preparation method thereof is as follows:
[0110] Step 1: Take 37.70 parts by mass of TDI, 1.57 parts by mass of HMDI, 54.85 parts by mass of PTMEG1000 and 5.88 parts by mass of DEG to react to obtain an isocyanate-terminated prepolymer, heat to 25-65°C, and degas for 2 hours under vacuum (-0.095MPa) to remove the gas and small molecular compounds in the prepolymer; then add 1.34 parts by mass of hollow microsphere polymer 920DE 40d30, stir to make the hollow microsphere polymer uniformly dispersed in the prepolymer, degas again under vacuum (-0.095MPa) for 2 hours, and set aside. The unreacted NCO in the isocyanate-terminated prepolymer is 9.4%.
[0111] Step 2: 26.08 parts by mass of MOCA was heated to 115° C. for standby use, wherein the stoichiometric ratio of NH2 in MOCA to NCO of the isocyanate-terminated prepolymer was 87%.
[0112] Step 3: Mix the prepolymer and curing agent under high-speed shearing, then cast into a round mold to form a casting block with a thickness of 12 cm, let it stand at room temperature for 10 minutes, and then place it in a 100°C oven for curing for 16 hours. After curing, it is automatically cooled to room temperature in the oven and then cut into thin sheets with a thickness of 80 mil.
[0113] Step 4: The groove selection uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30mil, groove width 20mil, groove spacing 120mil, and the center blank area diameter is 5 inches. After grooving, it is the polishing layer T1.
[0114] Step 5: Use double-sided tape (purchased from Sekisui Chemical Co., Ltd. and 3M Company) for the intermediate glue and the back glue layer, use the intermediate glue to bond the above-mentioned polishing layer T1 to the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer), and you can get the polishing pad P1, wherein the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA IV).
[0115] Example 2
[0116] This embodiment provides a polishing pad, and the preparation method thereof is as follows:
[0117] Step 1: Take 32.55 parts by mass of TDI, 8.1 parts by mass of HMDI, 57.35 parts by mass of PTMEG650 and 5.88 parts by mass of DEG to react to obtain an isocyanate-terminated prepolymer, heat to 25-65°C, and degas for 2 hours under vacuum (-0.095MPa) to remove the gas and small molecular compounds in the prepolymer; then add 1.97 parts by mass of hollow microsphere polymer 920DE 40d30, stir to make the hollow microsphere polymer uniformly dispersed in the prepolymer, degas again under vacuum (-0.095MPa) for 2 hours, and set aside. The unreacted NCO in the isocyanate-terminated prepolymer is 9.3%.
[0118] Step 2: 25.73 parts by mass of MOCA was heated to 115° C. for standby use, wherein the stoichiometric ratio of NH2 in MOCA to NCO of the isocyanate-terminated prepolymer was 87%.
[0119] Step 3: Mix the prepolymer and curing agent under high-speed shearing, then cast into a round mold to form a casting block with a thickness of 12 cm, let it stand at room temperature for 10 minutes, and then place it in a 100°C oven for curing for 16 hours. After curing, it is automatically cooled to room temperature in the oven and then cut into thin sheets with a thickness of 80 mil.
[0120] Step 4: The groove selection uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30mil, groove width 20mil, groove spacing 120mil, and the diameter of the center blank area is 5 inches. After grooving, it is the polishing layer T2.
[0121] Step 5: Use double-sided tape (purchased from Sekisui Chemical Co., Ltd. and 3M Company) for the intermediate glue and the back glue layer, use the intermediate glue to bond the above-mentioned polishing layer T2 to the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer) to obtain the polishing pad P2, wherein the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA IV).
[0122] Example 3
[0123] This embodiment provides a polishing pad, and the preparation method thereof is as follows:
[0124] Step 1: Take 32.98 parts by mass of TDI, 8.54 parts by mass of HMDI, 56.13 parts by mass of PTMEG650 and 2.35 parts by mass of DEG to react to obtain an isocyanate-terminated prepolymer, heat to 25-65°C, and degas for 2 hours under vacuum (-0.095MPa) to remove the gas and small molecular compounds in the prepolymer; then add 3.63 parts by mass of hollow microsphere polymer 920DET 40d25, stir to make the hollow microsphere polymer uniformly dispersed in the prepolymer, degas again under vacuum (-0.095MPa) for 2 hours, and set aside. The unreacted NCO in the isocyanate-terminated prepolymer is 9.5%.
[0125] Step 2: 26.36 parts by mass of MOCA was heated to 115° C. for standby use, wherein the stoichiometric ratio of NH2 in MOCA to NCO of the isocyanate-terminated prepolymer was 87%.
[0126] Step 3: Mix the prepolymer and curing agent under high-speed shearing, then cast into a round mold to form a casting block with a thickness of 12 cm, let it stand at room temperature for 10 minutes, and then place it in a 100°C oven for curing for 16 hours. After curing, it is automatically cooled to room temperature in the oven and then cut into thin sheets with a thickness of 80 mil.
[0127] Step 4: The groove selection uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30mil, groove width 20mil, groove spacing 120mil, and the diameter of the center blank area is 5 inches. After grooving, it is the polishing layer T3.
[0128] Step 5: Use double-sided tape (purchased from Sekisui Chemical Co., Ltd. and 3M Company) for the intermediate glue and the back glue layer, use the intermediate glue to bond the above-mentioned polishing layer T3 to the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer), and you can get the polishing pad P3, where the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA IV).
[0129] Example 4
[0130] This embodiment provides a polishing pad, and the preparation method thereof is as follows:
[0131] Step 1: Take 38.01 parts by mass of TDI, 1.97 parts by mass of HMDI, 54.08 parts by mass of PTMEG1000 and 5.94 parts by mass of DEG to react to obtain an isocyanate-terminated prepolymer, heat to 25-65°C, and degas for 2 hours under vacuum (-0.095MPa) to remove the gas and small molecular compounds in the prepolymer; then add 1.29 parts by mass of hollow microsphere polymer 920DE 80d30, stir to make the hollow microsphere polymer uniformly dispersed in the prepolymer, and degas again under vacuum (-0.095MPa) for 2 hours for standby use. The unreacted NCO in the isocyanate-terminated prepolymer is 9.7%.
[0132] Step 2: 26.90 parts by mass of MOCA was heated to 115° C. for standby use, wherein the stoichiometric ratio of NH2 in MOCA to NCO of the isocyanate-terminated prepolymer was 87%.
[0133] Step 3: Mix the prepolymer and curing agent under high-speed shearing, then cast into a round mold to form a casting block with a thickness of 12 cm, let it stand at room temperature for 10 minutes, and then place it in a 100°C oven for curing for 16 hours. After curing, it is automatically cooled to room temperature in the oven and then cut into thin sheets with a thickness of 80 mil.
[0134] Step 4: The groove selection uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30mil, groove width 20mil, groove spacing 120mil, and the diameter of the center blank area is 5 inches. After grooving, it is the polishing layer T4.
[0135] Step 5: Use double-sided tape (purchased from Sekisui Chemical Co., Ltd. and 3M Company) for the intermediate glue and the back glue layer, use the intermediate glue to bond the above-mentioned polishing layer T4 to the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer), and you can get the polishing pad P4, where the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA IV).
[0136] Example 5
[0137] This embodiment provides a polishing pad, and the preparation method thereof is as follows:
[0138] Step 1: Take 31.95 parts by mass of TDI, 8.40 parts by mass of HMDI, 57.88 parts by mass of PTMEG650 and 1.77 parts by mass of DEG to react to obtain an isocyanate-terminated prepolymer, heat to 25-65°C, and degas for 2 hours under vacuum (-0.095MPa) to remove the gas and small molecular compounds in the prepolymer; then add 0.83 parts by mass of hollow microsphere polymer 043DET 80d20, stir to make the hollow microsphere polymer uniformly dispersed in the prepolymer, degas again under vacuum (-0.095MPa) for 2 hours, and set aside. The unreacted NCO in the isocyanate-terminated prepolymer is 9.2%.
[0139] Step 2: 30.79 parts by mass of MOCA was heated to 115° C. for standby use, wherein the stoichiometric ratio of NH2 in MOCA to NCO of the isocyanate-terminated prepolymer was 105%.
[0140] Step 3: Mix the prepolymer and curing agent under high-speed shearing, then cast into a round mold to form a casting block with a thickness of 12 cm, let it stand at room temperature for 10 minutes, and then place it in a 100°C oven for curing for 16 hours. After curing, it is automatically cooled to room temperature in the oven and then cut into thin sheets with a thickness of 80 mil.
[0141] Step 4: The groove selection uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30mil, groove width 20mil, groove spacing 120mil, and the diameter of the center blank area is 5 inches. After grooving, it is the polishing layer T5.
[0142] Step 5: Use double-sided tape (purchased from Sekisui Chemical Co., Ltd. and 3M Company) for the intermediate glue and the back glue layer, use the intermediate glue to bond the above-mentioned polishing layer T5 to the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer), and you can get the polishing pad P5, where the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA IV).
[0143] Example 6
[0144] This embodiment provides a polishing pad, and the preparation method thereof is as follows:
[0145] Step 1: Take 39.34 parts by mass of TDI, 54.85 parts by mass of PTMEG1000 and 5.81 parts by mass of DEG to react to obtain an isocyanate-terminated prepolymer, heat to 25-65°C, and degas for 2 hours under vacuum (-0.095MPa) to remove the gas and small molecular compounds in the prepolymer; then add 0.46 parts by mass of hollow microsphere polymer 920DE40d30, stir to make the hollow microsphere polymer uniformly dispersed in the prepolymer, degas again under vacuum (-0.095MPa) for 2 hours, and set aside. The unreacted NCO in the isocyanate-terminated prepolymer is 9.8%.
[0146] Step 2: 32.62 parts by mass of MOCA was heated to 115° C. for standby use, wherein the stoichiometric ratio of NH2 in MOCA to NCO of the isocyanate-terminated prepolymer was 105%.
[0147] Step 3: Mix the prepolymer and curing agent under high-speed shearing, then cast into a round mold to form a casting block with a thickness of 12 cm, let it stand at room temperature for 10 minutes, and then place it in a 100°C oven for curing for 16 hours. After curing, it is automatically cooled to room temperature in the oven and then cut into thin sheets with a thickness of 80 mil.
[0148] Step 4: The groove selection uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30mil, groove width 20mil, groove spacing 120mil, and the center blank area diameter is 5 inches. After grooving, it is the polishing layer T6.
[0149] Step 5: Use double-sided tape (purchased from Sekisui Chemical Co., Ltd. and 3M Company) for the intermediate glue and the back glue layer, use the intermediate glue to bond the polishing layer T6 and the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer), and you can get the polishing pad P6, where the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA IV).
[0150] Example 7
[0151] This embodiment provides a polishing pad, and the preparation method thereof is as follows:
[0152] Step 1: Take 32.98 parts by mass of TDI, 8.54 parts by mass of HMDI, 56.13 parts by mass of PTMEG650 and 2.35 parts by mass of DEG to react to obtain an isocyanate-terminated prepolymer, heat to 25-65°C, and degas for 2 hours under vacuum (-0.095MPa) to remove the gas and small molecular compounds in the prepolymer; then add 3.02 parts by mass of hollow microsphere polymer 920DE 40d30, stir to make the hollow microsphere polymer uniformly dispersed in the prepolymer, degas again under vacuum (-0.095MPa) for 2 hours, and set aside. The unreacted NCO in the isocyanate-terminated prepolymer is 9.5%.
[0153] Step 2: 26.36 parts by mass of MOCA was heated to 115° C. for standby use, wherein the stoichiometric ratio of NH2 in MOCA to NCO of the isocyanate-terminated prepolymer was 87%.
[0154] Step 3: Mix the prepolymer and curing agent under high-speed shearing, then cast into a round mold to form a casting block with a thickness of 12 cm, let it stand at room temperature for 10 minutes, and then place it in a 100°C oven for curing for 16 hours. After curing, it is automatically cooled to room temperature in the oven and then cut into thin sheets with a thickness of 80 mil.
[0155] Step 4: The groove selection uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30mil, groove width 20mil, groove spacing 120mil, and the diameter of the center blank area is 5 inches. After grooving, it is the polishing layer T7.
[0156] Step 5: Use double-sided tape (purchased from Sekisui Chemical Co., Ltd. and 3M Company) for the intermediate glue and the back glue layer, use the intermediate glue to bond the above-mentioned polishing layer T7 to the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer) to obtain the polishing pad P7, wherein the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA IV).
[0157] Example 8
[0158] This embodiment provides a polishing pad, and the preparation method is as follows:
[0159] Step 1: Take 76.5 parts by mass LF750D isocyanate-terminated prepolymer and 23.5 parts by mass of LFG963A isocyanate-terminated prepolymer was mixed, heated to 25-65°C, degassed under vacuum (-0.095MPa) for 2h, then 0.59 parts by mass of hollow microsphere polymer 920DE 40d30 was added, and the hollow microsphere polymer was uniformly dispersed in the prepolymer under stirring, and degassed again under vacuum (-0.095MPa) for 2h for standby use. The unreacted NCO in the isocyanate-terminated prepolymer was 8.3%.
[0160] Step 2: Keep the curing agent composition: 23.49 parts by mass of MOCA at 115° C. for standby use, wherein the stoichiometric ratio of NH2 in MOCA to NCO in the isocyanate-terminated prepolymer is 89%.
[0161] Step 3: The prepolymer and curing agent composition were mixed under high-speed shearing, and then cast into a circular mold to form a casting block with a thickness of 12 cm, which was left to stand at room temperature for 10 minutes, and then placed in a 100°C oven for curing for 16 hours. After curing, the prepolymer was automatically cooled to room temperature in the oven, and then cut into sheets with thicknesses of 80 mil, 50 mil, and 120 mil.
[0162] Step 4: Select a thin sheet with a thickness of 80 mils. The groove shape uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30 mils, groove width 20 mils, groove spacing 120 mils, and the diameter of the center blank area is 5 inches. After grooving, it is the polishing layer T8.
[0163] Step 5: Use double-sided tape (purchased from Sekisui Chemical Co., Ltd. and 3M Company) for the intermediate glue and the back glue layer, use the intermediate glue to bond the above-mentioned polishing layer T8 to the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer) to obtain the polishing pad P8, wherein the buffer layer uses a polyurethane-impregnated non-woven fabric material (SUBA).
[0164] Comparative Example 1
[0165] This comparative example provides a polishing pad, and the preparation method is as follows:
[0166] Step 1: Take 100 parts by mass LFG963A isocyanate-terminated prepolymer was heated to 25-65°C, degassed under vacuum (-0.095 MPa) for 2 hours, and then 1.51 parts by mass of hollow microsphere polymer 920DE 40d30 was added, and the hollow microsphere polymer was uniformly dispersed in the prepolymer under stirring, and degassed again under vacuum (-0.095 MPa) for 2 hours for standby use. The unreacted NCO in the isocyanate-terminated prepolymer was 5.8%.
[0167] Step 2: Mix the curing agent composition: MOCA 7.07 parts by mass at 115°C and polyether polyol HF505 (molecular weight 11400) 15.92 parts by mass and 800 (molecular weight 280) 5.31 parts by mass kept at 25-65°C for use. 800 and The stoichiometric ratio of the sum of the OH groups of HF505 to the NCO groups of the isocyanate-terminated prepolymer is 100%.
[0168] Step 3: The prepolymer and curing agent composition were mixed under high-speed shearing, and then cast into a circular mold to form a casting block with a thickness of 12 cm, which was left to stand at room temperature for 10 minutes, and then placed in a 100°C oven for curing for 16 hours. After curing, the prepolymer was automatically cooled to room temperature in the oven, and then cut into sheets with a thickness of 80 mil.
[0169] Step 4: Select a thin sheet with a thickness of 80 mils. The groove shape uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30 mils, groove width 20 mils, groove spacing 120 mils, and the diameter of the center blank area is 5 inches. After grooving, it becomes the polishing layer TD1.
[0170] Step 5: Use double-sided tape (purchased from Sekisui Chemical Co., Ltd. and 3M Company) for the intermediate glue and the back glue layer, use the intermediate glue to bond the polishing layer TD1 and the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer) to obtain the polishing pad PD1, wherein the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA).
[0171] Comparative Example 2
[0172] This comparative example provides a polishing pad, and the preparation method is as follows:
[0173] Step 1: Take 100 parts by mass LF667 isocyanate-terminated prepolymer was heated to 25-65°C, degassed under vacuum (-0.095 MPa) for 2 hours, and then 1.32 parts by mass of hollow microsphere polymer 920DE 40d30 was added, and the hollow microsphere polymer was uniformly dispersed in the prepolymer under stirring, and degassed again under vacuum (-0.095 MPa) for 2 hours for standby use. The unreacted NCO in the isocyanate-terminated prepolymer was 6.2%.
[0174] Step 2: Curing agent composition: polyether polyol HF505 (molecular weight 11400) 55.93 parts by mass and 800 (molecular weight 280) 9.11 parts by mass kept at 25-65°C for use. 800 and The stoichiometric ratio of the sum of the OH groups of HF505 to the NCO groups of the isocyanate-terminated prepolymer is 100%.
[0175] Step 3: The prepolymer and curing agent composition were mixed under high-speed shearing, and then cast into a circular mold to form a casting block with a thickness of 12 cm, which was left to stand at room temperature for 10 minutes, and then placed in a 100°C oven for curing for 16 hours. After curing, the prepolymer was automatically cooled to room temperature in the oven, and then cut into sheets with a thickness of 80 mil.
[0176] Step 4: Select a thin sheet with a thickness of 80 mils. The groove shape uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30 mils, groove width 20 mils, groove spacing 120 mils, and the diameter of the center blank area is 5 inches. After grooving, it becomes the polishing layer TD2.
[0177] Step 5: Use double-sided tape (purchased from Sekisui Chemical Co., Ltd. and 3M Company) for the intermediate glue and the back glue layer, use the intermediate glue to bond the polishing layer TD2 and the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer) to obtain the polishing pad PD2, wherein the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA).
[0178] Shore hardness of polishing layer
[0179] The REX digital display Shaw D type automatic measurement hardness tester and Bareiss digital display Shaw D type automatic measurement hardness tester are used for measurement. The sample to be tested is punched into a 3"×3" square sample. The thickness of the sample to be tested is not less than 5mm. The measuring point is at least 9mm away from any edge of the sample. The hardness value is measured at least 6mm apart on the same sample, and the maximum value is taken. The sample needs to be tested under a standard environment of 23±2℃ and humidity 50%±10%. The specific results are shown in Table 1.
[0180] Density of polishing layer
[0181] The calculation is performed according to the following formula: SG = m / v = m / (π(d / 2)^2*h), where m is the weight of the polishing layer, d is the diameter of the polishing layer, and h is the thickness of the polishing layer. The specific results are shown in Table 1.
[0182] Micro contact area ratio evaluation
[0183] Sample preparation: Wipe the surface of the polishing pad or polishing layer with anhydrous ethanol, then blow dry with an air gun, use a 10mm diameter mold to cut out a circle with a diameter of 10mm on the polishing pad or polishing layer to be tested, and ensure that the samples are taken in the same area. After sample preparation, observe whether the sample surface is flat; the area with grooves or the area without grooves on the surface of the polishing pad or polishing layer can be used. It should be noted that when taking the area with grooves, the area of the grooves needs to be deducted for data processing.
[0184] Sampling: Take 14 sets of photos on the surface of a 10mm round test sample. You can choose 6 sets of photos in the middle of the round test sample, and 4 sets of photos on the left and right. Figure 4 shown.
[0185] Sports device:
[0186] The Z-axis of the test system uses the GMT standard electric slide table (AXS60-A2NR-DD) from Taiwan, China, with a motion stroke of ±10mm, a table size of 60mm*60mm, and a unidirectional positioning accuracy of 15μm. The motion control department uses a combination of SMC30PLC controller and SMC72XL Hall control rod; the sensor uses an S-type force sensor (SMT1-10N, INTERFACE USA).
[0187] Optical device:
[0188] Inverted metallographic microscope (LC-230DZ, Shenzhen Lichuang Instrument Co., Ltd.).
[0189] Software Algorithm:
[0190] The polishing pad micro-contact measurement software based on MATLAB 2020a was used to calculate the micro-contact area ratio of the images taken by the metallographic microscope. The specific results are shown in Tables 1 and 2.
[0191] In the embodiment of the present invention, the microscopic contact area of the polishing pad or the polishing layer under three pressures of 1.85 psi, 9.25 psi and 16.65 psi is measured, and the microscopic contact area of the polishing pad or the polishing layer after passing through the grinding machine is measured, wherein the microscopic contact area ratio S11 (%) represents the microscopic contact area ratio of the 1.85 psi polishing pad or polishing layer. S15 (%) represents the microscopic contact area ratio of the 9.25 psi polishing pad or polishing layer. S19 (%) represents the microscopic contact area ratio of the 16.65 psi polishing pad or polishing layer; wherein, the microscopic contact area ratio S21 (%) represents the microscopic contact area ratio of the 1.85 psi polishing pad.S25 (%) represents the microscopic contact area ratio of the 9.25 psi polishing pad. S29 (%) represents the microscopic contact area ratio of the 16.65 psi polishing pad.
[0192] Polishing layer roughness
[0193] The surface roughness test was performed using a white light interferometer, where the roughness (μm) represents the roughness of the polishing layer. The specific results are shown in Table 1.
[0194] Table 1
[0195] serial number Polishing layer <![CDATA[Density (g / cm 3 )]]> Shore hardness (D) Roughness(μm) <![CDATA[Microscopic contact area ratio S11 (%)]]> <![CDATA[Microscopic contact area ratio S15 (%)]]> <![CDATA[Microscopic contact area ratio S19 (%)]]> ζ(S11-1.85psi) ζ(S15-9.25psi) Example 1 T1 0.80 61.0 9.1 0.152 0.452 0.715 0.190 0.565 Example 2 T2 0.71 59.6 9.2 0.165 0.485 0.797 0.232 0.683 Example 3 T3 0.50 46.1 11.4 0.380 0.677 0.881 0.759 1.354 Example 4 T4 0.81 65.9 9.1 0.153 0.444 0.721 0.189 0.548 Example 5 T5 0.82 66.3 9.0 0.152 0.440 0.715 0.185 0.537 Example 6 T6 0.98 71.1 7.7 0.138 0.372 0.630 0.140 0.380 Example 7 T7 0.60 53.9 10.5 0.172 0.533 0.833 0.286 0.888 Example 8 T8 0.94 64.2 7.5 0.141 0.389 0.651 0.150 0.414 Comparative Example 1 TD1 0.75 19.2 4.9 2.872 3.417 5.214 3.829 4.556 Comparative Example 2 TD2 0.81 7.1 4.4 2.458 3.211 5.079 3.035 3.965
[0196] In Table 1, ζ(S11-1.85psi) represents the contact coefficient, which is 100 times the ratio of the microscopic contact area rate of the polishing layer under a pressure of 1.85psi to the density of the polishing layer; ζ(S15-9.25psi) represents the contact coefficient, which is 100 times the ratio of the microscopic contact area rate of the polishing layer under a pressure of 9.25psi to the density of the polishing layer.
[0197] Table 2
[0198] serial number Polishing pad <![CDATA[Microscopic contact area ratio S21 (%)]]> <![CDATA[Microscopic contact area ratio S25 (%)]]> <![CDATA[Microscopic contact area ratio S29 (%)]]> Example 1 P1 0.303 0.706 1.173 Example 2 P2 0.322 0.740 1.265 Example 3 P3 0.440 0.815 1.347 Example 4 P4 0.302 0.703 1.195 Example 5 P5 0.307 0.704 1.200 Example 6 P6 0.301 0.633 1.066 Example 7 P7 0.356 0.807 1.304 Example 8 P8 0.308 0.670 1.098 Comparative Example 1 PD1 4.150 5.875 8.336 Comparative Example 2 PD2 3.785 5.558 8.096
[0199] Polishing performance evaluation of polishing pads
[0200] The polishing pads prepared in the examples and comparative examples were tested on a machine to evaluate the polishing performance. The test conditions were as follows:
[0201] The test machine is AMAT Refelxion (Modify 5Zone);
[0202] The polishing wafer was a 300 mm 3S20KTENTEOS (oxide) blanket wafer purchased from Novellus Systems, Inc.; the slurry used for polishing was CES333F slurry (purchased from Asahi Glass Company), the polishing conditions used included a platen speed of 92 rpm, a carrier speed of 93 rpm, a slurry flow rate of 230 ml / min, and a down pressure of 12.8 KPa (1.85 psi) and 63.8 KPa (9.25 psi), an I-PDA31G-3N diamond conditioning disc (purchased from Kinik Company) was used to condition the chemical mechanical polishing pad, and the removal rate was measured by KLA-Tencor, and the polishing pad could be processed by a grinder for polishing performance evaluation, and the removal rate (TEOS The grinding rate non-uniformity NU (%) at the down pressures of 12.8 KPa (1.85 psi) and 63.8 KPa (9.25 psi) is calculated.
[0203] Defect evaluation
[0204] The defects on the polished substrate after polishing are obtained using KLA-Tencor The SP2 defect inspection system was used to inspect the defect. The defect size was 0.16 μm. The 10th wafer was measured and the evaluation results are shown in Table 3.
[0205] Table 3
[0206]
[0207] It should be noted that, according to the explanation and elaboration of the above description, those skilled in the art to which the present invention belongs may also make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some equivalent modifications and changes to the present invention should also be within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the invention.
Claims
1. A polishing layer, characterized in that: The polishing layer is a uniform closed-cell elastomer formed by a polyurethane substrate with continuous pore separation. The surface of the polishing layer contains micro-protrusions, which are in substantial contact with the object to be polished to form a microscopic contact surface. When the polishing layer is under a pressure of 1psi to 20psi, the microscopic contact area ratio between the polishing layer and the object to be polished is between 0.01% and 5%.
2. The polishing layer according to claim 1, characterized in that When the polishing layer is under a pressure of 1 psi to 10 psi, the contact coefficient ζ=(microscopic contact area ratio between the polishing layer and the object to be polished / density of the polishing layer)*100, and the contact coefficient ζ is between 0.1 and 1.
2.
3. The polishing layer according to claim 1, characterized in that The roughness of the polishing layer is between 1 μm and 30 μm; preferably, the roughness of the polishing layer is between 2 μm and 15 μm.
4. The polishing layer according to claim 1, characterized in that The density of the polishing layer is between 0.4 g / cm 3 ~1.1g / cm 3 The hardness of the polishing layer is between 10D and 75D.
5. The polishing layer according to claim 1, characterized in that The polishing layer comprises a reaction product of an isocyanate-terminated prepolymer and a curing agent, wherein the isocyanate-terminated prepolymer comprises a reaction product of a multifunctional isocyanate and a polyol.
6. The polishing layer according to claim 5, characterized in that The polyfunctional isocyanate includes 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, p-xylylene diisocyanate, m-xylylene diisocyanate, ethylene diisocyanate, 2,2,4-triisocyanate, One or more combinations of methyl hexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, 1,4-cyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, and norbornane diisocyanate; preferably, the multifunctional isocyanate comprises one or more combinations of 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.
7. The polishing layer according to claim 5, characterized in that The polyol comprises one or more combinations of polytetramethylene ether glycol, polyethylene glycol, polypropylene glycol, ethylene glycol, butanediol, diethylene glycol, neopentyl glycol, 2-methyl-1,3-propanediol, hexanediol, 3-methyl-1,5-pentanediol, 1,4-cyclohexanedimethanol, homopolymers and / or copolymers of ethylene oxide and propylene oxide; preferably, the polyol comprises one or more combinations of polytetramethylene ether glycol, polypropylene glycol, diethylene glycol, homopolymers and / or copolymers of ethylene oxide and propylene oxide.
8. The polishing layer according to claim 5, characterized in that The curing agent includes a polyamine curing agent; the polyamine curing agent includes diethyltoluenediamine (DETDA), N,N'-dialkyldiaminodiphenylmethane, 3,5-diethyl-2,4-toluenediamine and its isomers (for example, 3,5-diethyl-2,6-toluenediamine), 3,5-dimethylthio-2,4-toluenediamine and its isomers, 4,4'-methylene-bis-(2-chloroaniline) (MOCA), 4,4'-bis-(sec-butylamino)-diphenylmethane, 1,4-bis-(sec-butylamino)-benzene, 4,4'-methylene-bis-(2-chloroaniline), 4,4'-methylene-bis-(3-chloro-2,6-diethylbenzene Amine) (MCDEA), polyoxytetramethylene-di-p-aminobenzoate; p,p'-methylenedianiline (MDA); metaphenylenediamine (MPDA); 4,4'-methylene-di-(2,6-diethylaniline) (MDEA), 4,4'-methylene-di-(2,3-dichloroaniline) (MDCA), 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, 2,2',3,3'-tetrachlorodiaminodiphenylmethane, propylene glycol-di-p-aminobenzoate or one or more combinations thereof; preferably, the polyamine curing agent is 4,4'-methylene-bis-(2-chloroaniline) (MOCA).
9. The polishing layer according to claim 5, characterized in that The unreacted NCO of the isocyanate-terminated prepolymer is between 8.0% and 9.5%, and the stoichiometric ratio of NH2 to NCO of the isocyanate-terminated prepolymer is between 80% and 105%.
10. A polishing pad, characterized in that: The polishing pad comprises the polishing layer, the intermediate adhesive layer, the buffer layer and the release film layer as described in any one of claims 1 to 9. Under a pressure of 1psi to 20psi, the microscopic contact area ratio between the polishing pad and the object to be polished is between 0.01% and 5%.
11. A polishing method, characterized in that: A polishing object is provided, wherein the polishing object is selected from at least one of a magnetic substrate, an optical substrate or a semiconductor substrate, a polishing pad as described in claim 10 is provided, dynamic contact is formed between the polishing surface of the polishing layer and the polishing object to polish the surface of the polishing object, and a dresser is used to dress the polishing surface.
Citation Information
Patent Citations
Chemical mechanical polishing pad
CN108789135A
Method for predicting morphology characteristics of polishing pad after mortar particle finishing
CN115519476A
Generator coil that is fused with cube or bead-shaped iron and wire or film-shaped copper
KR1020240003127A
Method and device for fabricating multi-layer nanoparticle using capillariy
KR1020250008217A
Soft And Conditionable Chemical Mechanical Polishing Pad
US20140120809A1